Traditional Knowledge of Ethno Medicinal Plants Used by Tribes of Gondia District in Maharashtra, India for Antimicrobial Activity - Nimbekar , Tulsidas; Sanghi , Dilip; Borkar , Devendra (Novel Aspects on Pharmaceutical Research Vol. 8, 2023)
This chapter highlights about traditional knowledge of ethno medicinal plants used by tribes of Gondia District in Maharashtra, India State for Antimicrobial activity. The ethnopharmacological approach toward the understanding and appraisal of traditional and herbal medicines is characterized by the inclusions of the social as well as the natural sciences. The recent focus on holistic approaches and systems biology in medicinal plant research represents the trend toward the description and the understanding of complex multi-parameter systems. An ethno-medico botanical survey was made during March 2010 to November 2011 to collect the information from unexplored part of Gondia district in Maharashtra, India. The study was done through structured questionnaires in consultation with the tribal practitioners. The study enlists the medicinal plants used by several tribes, vaidus, knowledgeable persons and locally available information from the common people. A total of 65 plant species belonging to different families were used to treat different infections. Tribals use common forest medicinal plants for the relief of various ailments and also to preserve and promote their health by practicing their own methods. These methods are being considered safe and with lesser side effects. The information about plant species, local name, parts used, mode of preparation, dosage and duration were documented. The traditional herbal formulations need further pharmacological investigation to prove their efficacy and also develop new drugs for the effective treatment of chronic diseases in both human and veterinary species.